Genotype-Dependent Interaction of Lentil Lines with Ascochyta lentis - Sari, Ehsan; Bhadauria, Vijai; Vandenberg, Albert; Banniza, Sabine (Frontiers in Plant Science, 2017)
Ascochyta blight of lentil is a prevalent disease in many lentil producing regions and can cause major yield and grain quality losses. The most environmentally acceptable and economically profitable method of control is to develop varieties with high levels of durable resistance. Genetic studies to date suggest that ascochyta blight resistance genes in lentil lines CDC Robin, ILL 7537, 964a-46 and ILL 1704 are non-allelic. To understand how different resistance genes manifest resistance in these genotypes and an accession of Lens ervoides, L-01-827A, with high level of resistance to ascochyta blight, cellular and molecular defense responses were compared after inoculation with the causal pathogen Ascochyta lentis. Pathogenicity testing of the resistant lines to A. lentis inoculation revealed significantly lower disease severity on CDC Robin and ILL 7537 compared to ILL 1704 and 964a-46, and no symptoms of disease were observed on L-01-827A. Histological examinations indicated that cell death triggered by the pathogen might be perturbed as a mechanism of resistance in CDC Robin. In contrast, limiting colonization of epidermal cells by A. lentis is a suggested mechanism of resistance in 964a-46. A time-series comparison of the expressions of hallmark genes in salicylic acid (SA) and jasmonic acid signal transduction pathways between CDC Robin and 964a-46 was conducted. These partially resistant genotypes differed in the timing and the magnitude of SA and JA signaling pathway activation. The SA signaling pathway was only triggered in 964a-46, whereas the JA pathway was triggered in both partially resistant genotypes CDC Robin and 964a-46. The expression of JA-associated genes was lower in 964a-46 than CDC Robin. These observations corroborate the existence of diverse ascochyta blight resistance mechanisms in lentil genotypes carrying different resistance genes.